The racial disparity among post transcatheter aortic valve replacement outcomes: A meta-analysis. (February 2023) - Jaiswal, Vikash; Peng Ang, Song; Hanif, Muhammad; Savaliya, Mittal; Vadhera, Ananya; Raj, Nishchita; Gera, Asmita; Aujla, Savvy; Daneshvar, Farshid; Ishak, Angela; Subhan Waleed, Madeeha; Hugo Aguilera-Alvarez, Victor; et al.
Abstract: Background: Racial disparities have been well described in cardiovascular disease. However, the impact of race on the outcomes post - Transcatheter aortic valve replacement (TAVR) remains unknown. Objective: We aim to evaluate the disparity among the race (black and white) post - TAVR. Methods: We systematically searched all electronic databases from inception until September 26, 2022. The primary outcome was in-hospital all-cause mortality, and secondary outcomes was myocardial infarction (MI), acute kidney injury (AKI), permanent pacemaker implantation (PPI) or ICD, stroke, vascular complications, and major bleeding. Results: A total of three studies with 1, 02, 009 patients were included in the final analysis. The mean age of patients with white and black patients was 82.65 and 80.45 years, respectively. The likelihood of in-hospital all-cause mortality (OR, 1.01(95 %CI: 0.86–1.19), P = 0.93), stroke (OR, 0.83(95 %CI:0.61–1.13), P = 0.23, I2 = 46.57 %], major bleeding [OR, 1.05(95 %CI:0.92–1.20), P = 0.46), and vascular complications [OR, 0.92(95 %CI:0.81–1.06), P = 0.26), was comparable between white and black patients. However, patients with white race have lower odds of MI (OR, 0.65(95 %CI:0.50–0.84), P < 0.001), and AKI (OR, 0.84(95 %CI:0.74–0.95), P = 0.01) and higher odds of PPI or ICD (OR, 1.16(95 %CI: 1.06–1.27), P < 0.001, I2 = 0 %) compared with black race patients. Conclusion: Our findings suggest disparity post - TAVR outcomes existed, and black patients are at higher risk of MI and AKI than white patients. Key Clinical Message: What is already known on this topic: Disparity has been witnessed among patients with cardiovascular disease. However, no studies have drawn a significant association among post-TAVR patients' outcomes What this study adds: Among patients who underwent TAVR, there is a difference in the adverse outcomes between black and white race patients. White patients have a lower risk of post-procedure MI and AKI compared with Black patients. How this study might affect research, practice, or policy: These disparities need to be addressed, and proper guidelines need to be made along with engaging patients with better medical infrastructure and treatment options. .